Physical Test Table Tennis Domain for 13-15 Years Age Group - Liskustyawati, Hanik (Sebelas Maret University, 2016)
Every sport requires a different level of physical qualities with the other, but very important note is the physical quality of players needed to achieve peak performance when desired. In the world of sport, to achieve high performance, optimal physical quality is a requirement that cannot be ignored. The value of minimum standards for each sport varies in accordance with the necessary physical qualities of the sport. Many types of physical ability test that is used for identification and development of the physical domain of table tennis game, but have not tested how much effectiveness against the appearance of table tennis. This preliminary study design is a development of this kind of research that is the development of table tennis test aged 13-15 years Central Java PTMSI player. In the limited testing performed tests a number of players made up 61 players that consist of 27 men and 31 women. From the results of Focus Group Discussion (FGD) trainers recommend as many as 25 kinds of tests for measuring the physical domain of table tennis. Based on the analysis of data using part-whole correlation analysis of the results obtained from Guilford: Validity and reliability test for men and women players are not different, both of them are on average of very good category.